Resveratrol induces vascular smooth muscle cell differentiation through stimulation of SirT1 and AMPK. - Anne Marie Thompson (Public Library of Science (PLoS), 2014)
Phenotypic plasticity in vascular smooth muscle cells (VSMC) is necessary for vessel maintenance, repair and adaptation to vascular changes associated with aging. De-differentiated VSMC contribute to pathologies including atherosclerosis and intimal hyperplasia. As resveratrol has been reported to have cardio- protective effects, we investigated its role in VSMC phenotypic modulation. We demonstrated the novel finding that resveratrol promoted VSMC differentiation as measured by contractile protein expression, contractile morphology and contraction in collagen gels. Resveratrol induced VSMC differentiation through stimulation of SirT1 and AMPK. We made the novel finding that low or high dose resveratrol had an initially different mechanism on induction of differentiation. We found that low dose resveratrol stimulated differentiation through SirT1-mediated activation of AKT, whereas high dose resveratrol stimulated differentiation through AMPK-mediated inhibition of the mTORC1 pathway, allowing activation of AKT. The health effects of resveratrol in cardiovascular diseases, cancer and longevity are an area of active research. We have demonstrated a supplemental avenue where-by resveratrol may promote health by maintaining and enhancing plasticity of the vasculature.